Status, adoption gap and way forward of pulses production in India - NAIN, M S; KUMBHARE, N V; SHARMA, J P; CHAHAL, V P; BAHAL, RAM (The Indian Journal of Agricultural Sciences, 2015)
Pulses are generally grown under rainfed, highly unstable and complex production environments, substantial variability in soil and environmental factors, high year to year output variability, and variation in soil moisture. One is required to emphasize the need for identifying and quantifying level of adoption and its determinants across agroclimatic regions. The net availability of pulses has come down from 60 g/day/capita in 1951 to 41.6 g/day/capita in 2012-13 due to stagnant production and rapid increase in population. Among so many, the most important way to increase production in the short-run is to reduce yield gaps between research station, on-farm demonstration and farmer's fields. The yield gap and constraint analysis was carried out for pigeonpea and chickpea in high potential high gap states and districts of India. The results showed high to medium level of adoption gaps in almost all the recommendation domains in both the crops. Nearly 80 percent of the respondents had not adopted manurial aspects of the crop and 76 percent had not gone for any plant protection measures. Only 29% adopted the recommended varieties and nearly 60% adopted agronomic practices like line sowing, weed management, spacing, presowing irrigation and proper land preparation. It can be recommended that in order to have the latest information on pulse improvements from researchers, it will be necessary to have appropriate training for the extension workers and subsequently to farmers with availability of matc11hing input supply system.